Kawin Sumbong: Eksplorasi Perkawinan Adat Jambi Menurut Hukum Positif Di Indonesia - Zezen Zainul Ali; Mega Puspita (Fakultas Syariah IAIN Madura, 2022)
This research will discuss the positive law in the tradition of sumbong marriages. Confused marriage is a marriage that is carried out internally within the scope of society (endogamy). Sumbong marriage consists of 12 types, of which the most dominant are marriages between anak pusako and paternal/male relatives. This kind of marriage is considered to have violated customary law and is subject to sanctions by paying one goat (anak pusako) and one buffalo (relatives). This research was conducted using a juridical-sociological approach to the Lekuk Lima Puluh Tumbi Lempur community, Jambi. The research finding is that contemptuous marriage does not conflict with positive law and religious law. The customary sanction for consumptive marriage is meant to expand kinship ties. Customary law and positive law in conjugal marriage synergize and go hand in hand if customary law does not conflict with the applicable positive law.